LEARNING INNOVATION IN THE MIDDLE OF A PANDEMIC: WHAT ARE THE PERCEPTIONS OF STUDENTS, TEACHERS AND PARENTS? - Annisa, Hizza Sara; Widodo, Arif (PGSD UNIKA SANTU PAULUS RUTENG, 2022)
Online learning is one of the biggest innovations in the world of education in the pandemic era. All levels of education have implemented online learning, including in this case elementary school. This study aims to determine the perceptions of students, teachers, and parents in the application of online learning in elementary schools. The type of research used is descriptive qualitative. Data collection through questionnaires and interviews. The informants in this study were thirty-five elementary school students, one teacher, and four parents. The research was conducted at one of the elementary schools in the East Lombok district. The results of the study indicate that most students do not like online learning, many students have difficulty in learning online, lack focus in learning, cannot understand the subject matter well, and find it difficult to do assignments. In the perspective of online learning, teachers are considered to have many obstacles, one of the most severe obstacles is the use of technology and difficulties in explaining the subject matter to students properly. Parents' perceptions of online learning include online learning that costs more and adds to the burden on parents, especially when they have to help students do schoolwork at home. Student learning activities in online learning are less than optimal, students spend more time playing than studying. Based on the results of this study, shows that innovation in learning during a pandemic has many challenges. Serious intervention is needed to change the way all stakeholders think about online learning.